Strategic communication: US-Philippines relations and the American rebalancing strategy - Misalucha, Charmaine G. (Animo Repository, 2014)
From 2011, the Barack Obama Administration made a series of announcements that the United States was shifting its attention away from Iraq and Afghanistan and towards Asia (Obama 2011). This rebalancing, it has been argued, is a ‘natural trend’ that focuses on the up-and-coming, dynamic region of the world (Cronin 2012: 12). At the same time, this new policy was seen as a counter-narrative to American decline, as well as a way to balance the rapid growth, strength and inﬂuence of China in the region (McDevitt 2012). While the strategy was multi-faceted, tensions in the South China Sea overshadowed its diplomatic and economic rationale and made it, at least insofar as the Philippines is concerned, ‘a decidedly military eﬀort’ (Bitzinger 2012: 35, emphasis in original). The American rebalancing strategy is much broader than a mere resuscitation of the US-Philippines security relationship. American strategic moves that are hallmarks of the rebalancing strategy include the deployment of 2,500 US Marines for training purposes in Darwin, the stationing of four new littoral combat ships at the Changi Naval Base in Singapore, plans for temporary basing access in the Philippines, and an increase in the number of ships in the Paciﬁc Fleet. Such moves, however, do not deﬁnitively pin down the strategy’s overall meaning and content (Glosserman 2013). I argue that until that is accomplished, the US rebalancing strategy will remain cloaked in ambiguity. Interestingly, despite the ambiguity surrounding the rebalancing strategy and its motivations, the United States has been able to implement successfully its basic concept. If we strip away the diplomatic, economic and military aspects of the rebalancing strategy, we are left with several basic premises: that the United States is ‘back’ in the region, that it is prioritizing Asia, and that it has a stake in helping to shape the region’s future security architecture. A good measure of the persuasiveness of this idea is not just that it was ‘sold’ in a narrative that is both cohesive and shaped against the backdrop of an empirical reality, but also that it was ‘bought’ by the Philippines, a renowned American treaty ally. The selling and buying of ideas in international relations is a paramount requirement for eﬀective international security relations. In this case, that requirement seems well on its way to being fulﬁlled.